Vinylboronic Acids as Fast Reacting, Synthetically Accessible, and Stable Bioorthogonal Reactants in the Carboni–Lindsey Reaction. (8th September 2016) - Eising, Selma; Lelivelt, Francis; Bonger, Kimberly M.
Abstract: Bioorthogonal reactions are widely used for the chemical modification of biomolecules. The application of vinylboronic acids (VBAs) as non‐strained, synthetically accessible and water‐soluble reaction partners in a bioorthogonal inverse electron‐demand Diels–Alder (iEDDA) reaction with 3, 6‐dipyridyl‐ s ‐tetrazines is described. Depending on the substituents, VBA derivatives give second‐order rate constants up to 27 m −1 s −1 in aqueous environments at room temperature, which is suitable for biological labeling applications. The VBAs are shown to be biocompatible, non‐toxic, and highly stable in aqueous media and cell lysate. Furthermore, VBAs can be used orthogonally to the strain‐promoted alkyne–azide cycloaddition for protein modification, making them attractive complements to the bioorthogonal molecular toolbox.